Impact of Behavioral Problems to Special Needs Pupils - Dardha, Donika; Burda, Mariela; Piluri, Aleksandra (Mediterranean Journal of Social Sciences, 2012)
The object of this study is to investigate the impact of behavioural problems on the special needs of pupils and tocome up with some teaching strategies well-suited to these needs. The judgements that teachers make about the special needsof pupils are influenced by their distinctive behavior and movements, the way their attention is distracted and their inability towork in groups. The successful integration of children with learning difficulties depends less on the gravity of the learningproblems and is more influenced by the behaviour of the child. If the child follows the rules of his school, he/she does not troublethe teachers and fellow-students, is keen to participate and exhibits a high level of self-management and concentration whileperforming his tasks. This study will focus on the most common problems found in schools: aggressive behaviour, a low level ofconcentration, emotional problems, etc. Such behaviour is called primary not only because of its frequency, but also because ofits consequences on the learning of the student himself and that of his fellow-student. The methods and strategies that modifybehaviour like: the participation of students, the concentration of attention, the management of difficult situations, the cultivationof a good opinion of oneself influence the achievements of the students and the way they use their time at school.